Feasibility of a blind perineural injection technique for brachial plexus blockade in eastern box turtles (Terrapene carolina carolina): a cadaver study. (September 2021) - Mones, Alissa B.; Gorges, Melinda A.; Santangelo, Stephen M.; Lewbart, Gregory A.; Harrison, Tara M.; Gerard, Mathew P.
Abstract: Objective: To describe the anatomy of the brachial plexus in eastern box turtles ( Terrapene carolina carolina ), develop a blind perineural injection technique for brachial plexus blockade and evaluate the distribution of three volumes of new methylene blue dye for injection in cadavers. Study design: Prospective, randomized, blinded cadaveric study. Animals: A total of 24 frozen-thawed box turtle cadavers; two turtles identified with shoulder injuries were subsequently excluded from the study. The remaining 22 turtles weighed 397 (190–581) g, median (range). Methods: The brachial plexus and regional anatomy were identified by dissection of seven cadavers to determine anatomic landmarks for a perineural injection technique. This technique was tested by randomizing 15 cadavers into one of three groups to be injected bilaterally with one of three volumes (0.1, 0.2 or 0.3 mL) of methylene blue dye 1% aqueous solution. Investigators blinded to the assigned group dissected cadavers 15 minutes after injection and used staining of the four cervical spinal nerves (C5–C8; 25% for each nerve) to record a staining score of the brachial plexus (0–100%). Results: Based on descriptions of the anatomy of the brachial plexus, an injection technique was designed. Injections of 0.1 mL methylene blue dye resulted in nine/10 injections with 100% nerve stained, and one/10 injection with 50% (two) nerves stained. All injections of 0.2 or 0.3 mL of methylene blue dye resulted in 100% nerves stained. Conclusions and clinical relevance: Perineural injection of the brachial plexus with 0.1, 0.2 or 0.3 mL methylene blue dye was successful in 29/30 injections in box turtle cadavers weighing 190–581 g. Further studies are needed to determine the minimum volume of injectate that can be successfully used for this technique, and to evaluate its application and efficacy in live turtles.